Fangchinoline inhibits non-small cell lung cancer metastasis by reversing epithelial-mesenchymal transition and suppressing the cytosolic ROS-related Akt-mTOR signaling pathway. (1st September 2022) - Chen, Bonan; Song, Yue; Zhan, Yujuan; Zhou, Shikun; Ke, Junzi; Ao, Weizhen; Zhang, Yigan; Liang, Qiqi; He, Minhui; Li, Shuhui; Xie, Fuda; Huang, Haonan; et al.
Abstract: Few drugs alleviate non-small cell lung cancer (NSCLC) metastasis effectively. Small molecular screening demonstrated that fangchinoline (Fan) reversed epithelial-mesenchymal transition (EMT) in NSCLC cells, inhibiting cell invasion and migration. RNA sequencing (RNA-seq) of Fan-treated NSCLC cells revealed that Fan potently quenched the NADP + metabolic process. Molecular docking analysis revealed that Fan directly and specifically targeted NOX4. NOX4 was associated with poor prognosis in NSCLC in both The Cancer Genome Atlas (TCGA) and Hong Kong cohorts. In mitochondrial DNA-depleted ρ 0 NSCLC cells, Fan decreased cytosolic reactive oxygen species (ROS) to inhibit the Akt-mTOR signaling pathway by directly promoting NOX4 degradation. In TCGA and Hong Kong cohorts, NOX4 upregulation acted as a driver event as it positively correlated with metastasis and oxidative stress. Single-cell RNA-seq indicated that NOX4 was overexpressed, especially in cancer cells, cancer stem cells, and endothelial cells. In mice, Fan significantly impeded subcutaneous xenograft formation and reduced metastatic nodule numbers in mouse lung and liver. Drug sensitivity testing demonstrated that Fan suppressed patient-derived organoid growth dose-dependently. Fan is a potent small molecule for alleviating NSCLC metastasis by directly targeting NOX4 and is a potential novel therapeutic agent. Graphical abstract: Image 1 Highlights: Fangchinoline reversed EMT to inhibit NSCLC cell invasion and migration. Fangchinoline decreased NOX4-derived cytosolic ROS to inhibit the Akt-mTOR pathway. Fangchinoline directly and specifically targeted NOX4. NOX4 is an ideal druggable target in NSCLC.